Research on Growth and Fruit Quality of Vitis Vinifera L.cv.Moldova with Different Irrigation Volume - CHEN Tuo; ZHANG Qingtao; CEHN Yixuan; WANG Zhenping (Renmin Zhujiang)
In order to develop a suitable irrigation plan for Vitis vinifera L.cv.Moldova,base on microfiber wicking infiltration irrigation,this paper conducts a single-factor three-level randomized block test,with the water volume of 90L (A30*3),60L (A30*2) and 30L (A30*1),and studies the growth and fruit quality of Vitis vinifera L.cv.Moldova with different irrigation volume under microfiber wicking infiltration irrigation.The experimental results show that:Increasing water amount promoted the growth and fruit quality of Vitis vinifera L.cv.Moldova,especially for the treatment A30*3.The lateral shoot growth and fruit size for A30*3 and A30*2 were higher than A30*1.The berry weight for the treatment A30*3 was 25.5% and 30.0% higher than A30*2 and A30*1,respectively.The sugar-acid ratio for A30*2 was highest in all treatments.Contents of Vitamin C for A30*2 and A30*1 were higher than A30*3,but soluble protein showed the opposite order.Therefore,it can be concluded that increasing the irrigation volume can promote the growth and fruit quality of Vitis vinifera L.cv.Moldova under microfiber wicking infiltration irrigation.The treatment A30*3 provided suitable irrigation volume in this test.